STUDENTS’ PERSPECTIVES ON THE IMPACT OF ARTIFICIAL INTELLIGENCE IN LEARNING BUSINESS ENGLISH - Cristina Laura ABRUDAN (Oradea Journal of Business and Economics, 2025)
The intrinsic link between the development of technology and the future of higher education is no longer a doubt. New possibilities along with new challenges both for teaching and for learning change the landscape of education and the possibilities of it. It is well-known that technology advancements, especially the appearance of the Artificial Intelligence has brought about huge changes in the trends of teaching English. This article explores the traditional trends and the future trends of Business English teaching, focusing on the pedagogical shifts imposed by the technological advancements in education, from the students’ perspectives. More exactly, this research article explores the landscape of teaching Business English focusing both on current trends and on future approaches, the usefulness and the effectiveness of engaging new technology in classes. It is based on mixed-methods research including a systematic literature review and semi-structured interviews, in the qualitative phase, as an instrument for data collection, aiming to find out the students’ perspective towards the use of modern technology-based methods in comparison with traditional methods of learning/teaching Business English. The sample of the study consists of 50 students at the Faculty of Economic Sciences, University of Oradea, first and second year of Bachelor’s Degree. The students have been asked 5 sets made up of 3 questions on their opinions towards using technology in learning Business English. The study explores the following three main topics: background and experience with AI, perceptions and attitudes, usage and application, effectiveness and learning impact, challenges and concerns. The results show that a significant integration of technology in what is known as blended learning has resulted in a boost in learning Business English, being more interactive, engaging and effective. The students feel that their skills (productive skills: speaking and writing and the receptive skills: reading and listening) have improved after a period of using technology-based tools in the teaching and learning process. Thus, the results show that technology represents one of the most appreciated and appropriate learning tools for today’s Generation Z, improving learning effectiveness and evaluation validity.